Anti-inflammatory compounds of macro algae origin: A review - Jaswir, Irwandi; A. Monsur, Hammed (Academic Journals, 2011)
Inflammation, occurs frequently in living tissues, and is responsible for numerous death and precursor to some deadly diseases. This review focus on seaweed derived anti-inflammatory compounds, which have attracted interest and promising replacer of current anti-inflammatory drugs. Macro algae have both pro- and anti-inflammatory compounds, the later include sulphated polysaccharides (fucoidans) from brown seaweeds, alkaloids (Caulerpin I, II and III) from red and green seaweeds, polyunsaturated fatty acids (Docosahexaenoic acid: EDA, Eicosapentaenoic acid: EPA, Stearidonic acid: SA and Eicosatrienoic acid: ETA), carotenoids (fucoxanthin and astaxanthin), Pheophytin A and Vidalols A and B. Anti-inflammatory assays include edema, erythema, tumor necrosis factor (TNF-α), interleukin (IL 1β, 6, 8), Nitric oxide (NO), inducible Nitric oxide synthase (iNOS), Prostaglandin E (PGE 2 and 3), Cyclooxygenase (COX-2), transcription factor (NF-κB) and leukotrienes (LB 3 and 4). Although, in-vivo and in-vitro studies have been done for crude extracts and specific compounds, but some compounds have not analysed in-vitro, and investigation of their pathway need to be studied.